Family activity and eating habits questionnaire - Donisthorpe, Nicole Ann (Montana State University - Bozeman, College of Nursing, 2012)
The nationwide health concern of childhood obesity directly affects the western rural state of Montana. From 1990 to 2007, the childhood obesity rate in Montana has grown from affecting nine percent of the population of children to twenty-seven present (Daphane, 1990; NICH, 2007). The study's purpose is to examine family eating and activity habits that directly impact the likelihood of a child to develop childhood obesity including activity level, stimulus exposure, eating related to hunger, and eating styles. The instrument used in this research study was the Family Eating and Activity Habits Questionnaire contained four subcategories including activity level, stimulus exposure, eating related to hunger, and eating style. The Family Eating and Activity Habits Questionnaire use a wide variety of fill in the blank questions and rating scales in order to examine each of the subcategories. The specific target population for this study was parents who reside in the western rural state of Montana based on a convenience sample. The sample population was parents, with children between the ages of five to thirteen, who were willing to complete a parental questionnaire. The parental questionnaires were distributed in March and April of 2011 in two elementary schools. After the parental questionnaires were collected, the parental questionnaire scores were measured by adding up the mean of each score; the mother, father, child, and total family score. The central tendency of the data was analyzed and compared with the mean total score establish in the previous Family Activity and Eating Habit Questionnaire results. In the activity level section, the M score was 21.8. The SD computed was 22.96. In the stimulus exposure section, the M score was 10.7. The SD computed was 4.05. In the eating related to hunger section, the M score was 5.5. The SD computed was 2.42. In the eating styles section, the M score was 42. The SD computed was 15.07. In the overall scoring of the survey, the M score was 80. The results of overall score indicate that the higher the total scores, the less appropriate the eating and activity patterns.
Keywords: Obesity; Children; Food habits; Exercise